The unheard truth : poverty and human rights - Khan, Irene; Petrasek, David; Annan, Kofi A. (Kofi Atta) (New York, N.Y. : W.W. Norton & Co., 2009)
"Despite economic growth in almost every corner of the world over the last decade, billions of people still live in poverty. Amnesty International Secretary General Irene Khan claims that economic analyses do not provide a full picture and economic solutions alone cannot end the problems of poverty. In an argument enriched with her personal experiences and case studies from around the world, Khan sees poverty as the world's worst human rights crisis because it traps people in a vicious cycle of deprivation, insecurity, exclusion, and voicelessness. She argues that the foremost challenge is the empowerment of poor people, and makes a passionate and urgent plea for action to uphold human rights in the fight to end poverty."--BOOK JACKET.
The world's worst human rights crisis -- Freedom and its critics : why 'voice' matters -- Freedom from discrimination : ending exclusion -- Living in fear : securing rights -- Poverty trapped -- Needless deaths : the right to safe motherhood -- The global slum : winning the right to the city -- Commodities boom, rights bust -- Claiming rights : legal empowerment to end poverty -- From acknowledgment to action : a campaign for the rights of poor people.
Includes bibliographical references and index.
Keywords: Poverty; Poor; Human rights